1997
DOI: 10.1002/pro.5560061012
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione S‐transferase can be used as a C‐terminal, enzymatically active dimerization module for a recombinant protease inhibitor, and functionally secreted into the periplasm of Escherichia coli

Abstract: Glutathione S-transferase (GST) from Schistosoma juponicum, which is widely used for the production of fusion proteins in the cytoplasm of Escherichia coli, was employed as a functional fusion module that effects dimer formation of a recombinant protein and confers enzymatic reporter activity at the same time. For this purpose GST was linked via a flexible spacer to the C-terminus of the thiol-protease inhibitor cystatin, whose binding properties for papain were to be studied. The fusion protein was secreted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(22 citation statements)
references
References 25 publications
1
21
0
Order By: Relevance
“…Many lines of evidence suggest either GST or the GST-domains of fusion proteins have the potential to mediate oligomerization both in vitro and in vivo (23,24). In particular, Tudyka and Skerra mentioned that one should remember many proteins require an intact N-terminus for their bio-chemical activity when considering the use of GST as a permanent rather than transient fusion partner (24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many lines of evidence suggest either GST or the GST-domains of fusion proteins have the potential to mediate oligomerization both in vitro and in vivo (23,24). In particular, Tudyka and Skerra mentioned that one should remember many proteins require an intact N-terminus for their bio-chemical activity when considering the use of GST as a permanent rather than transient fusion partner (24).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, Tudyka and Skerra mentioned that one should remember many proteins require an intact N-terminus for their bio-chemical activity when considering the use of GST as a permanent rather than transient fusion partner (24). Regarding hydrophobicity, previous studies have shown the first 12 N-terminal amino acids of HK II (the mitochondrial binding domain) along with the first 11 N-terminal amino acids of HK I are very hydrophobic and may influence the kinetic properties of the enzyme (12).…”
Section: Discussionmentioning
confidence: 99%
“…Branch Migration Assay-The hRad54 protein (100 nM, unless indicated otherwise) was incubated with 32 P-labeled synthetic PX-junction (number 71/169/170/171) (33 nM, molecules), 32 P-labeled synthetic X-junction (number 71/170/234/ 235) (33 nM, molecules), or 32 P-labeled synthetic PX-junction (number 265/266/269/270) (20 or 30 nM, molecules) in a 90-l branch migration buffer containing 25 mM Tris acetate, pH 7.5, 2 mM ATP, 1 mM dithiothreitol, 100 g/ml bovine serum albumin, the ATP-regenerating system (10 units/ml creatine phosphokinase and 15 mM creatine phosphate), and the indicated concentrations of magnesium acetate. The reactions were carried out at 30°C or in the case of PX-junction (number 265/ 266/269/270) at 20°C.…”
mentioning
confidence: 99%
“…This property is very different from free GST, 100% of which migrated as dimers after being crosslinked (22). Therefore, primase with a GST tag is a stable monomer under reducing conditions but is capable of forming large crosslinked networks under oxidizing conditions.…”
Section: Resultsmentioning
confidence: 94%